2022
DOI: 10.31234/osf.io/gca56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a positive relationship between perceived stress and belief in conspiracy theories

Abstract: Perceived stress has previously been implicated in the belief of conspiracies, with some authors suggesting that stress can precipitate increased belief in conspiracy theories. This preregistered survey study aimed to replicate findings by Swami et al. (2016) showing a positive correlation between belief in conspiracy theories and perceived stress. 372 Australian and New Zealand residents participated. Beliefs in conspiracy theories were measured using 11 items drawn mainly from existing scales (α = .87). Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As stated in the hypothesis, a positive relationship between conspiracy beliefs and stress is expected to exist. However, while some studies (Constantinou et al 2021;Simione et al 2021;Swami et al 2016;Williams et al 2022) found a significant positive relationship, other studies (Ferreira et al 2022;Georgiou et al 2020) could not find a significant relationship. In the model estimated in this study, the effect of conspiracy beliefs on stress was found to be insignificant.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As stated in the hypothesis, a positive relationship between conspiracy beliefs and stress is expected to exist. However, while some studies (Constantinou et al 2021;Simione et al 2021;Swami et al 2016;Williams et al 2022) found a significant positive relationship, other studies (Ferreira et al 2022;Georgiou et al 2020) could not find a significant relationship. In the model estimated in this study, the effect of conspiracy beliefs on stress was found to be insignificant.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, there is uncertainty about whether there is a relationship between stress and belief in conspiracy theories. While some studies (Constantinou et al 2021;Simione et al 2021;Swami et al 2016) found a positive and significant relationship, some studies (Ferreira et al 2022;Georgiou et al 2020) found no significant relationship (Williams et al 2022).…”
Section: Vaccine Hesitancy and Associated Factorsmentioning
confidence: 99%